Quantification of physical activity with prospective activity tracking after transfemoral aortic valve replacement. (1st April 2023) - Haum, Magda; Humpfer, Fabian; Steffen, Julius; Fischer, Julius; Stocker, Thomas J.; Sadoni, Sebastian; Theiss, Hans; Braun, Daniel; Orban, Martin; Rizas, Konstantinos; Massberg, Steffen; Hausleiter, Jörg; et al.
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is a well-established, safe and effective therapy for severe symptomatic aortic stenosis (AS). The aim of this study was to objectively quantify improvement of physical activity after TAVR, with consideration of different low-gradient AS subtypes. Methods and results: All patients undergoing TAVR for severe AS were screened. Participants received a wearable activity tracker (Fitbit®) at hospital discharge following TAVR and 6 months thereafter. The difference of median daily steps was defined as surrogate outcome for physical activity. For analysis, patients were grouped into high-gradient (HG) AS (dPmean ≥40 mmHg), classical low-flow low-gradient (LFLG) AS (dPmean <40 mmHg, EF <50%), paradoxical LFLG-AS (dPmean <40 mmHg, EF ≥50%, SVi ≤35 ml/m2) and normal-flow low-gradient (NFLG) AS (dPmean <40 mmHg, EF ≥50%, SVi >35 ml/m2) according to mean transvalvular pressure gradient (dPmean), stroke volume index (SVi) and left-ventricular ejection fraction (LVEF). Results and conclusions: The analysis is based on 230 patients. The median daily step count was 4409 [IQR 2581–7487] after hospital discharge and 5326 [IQR 3045–8668] 6 months thereafter. Median difference of daily steps was ∆529 [IQR -702-2152]). Patients with HG-AS and paradoxical LFLG-AS showed a significant improvement of daily steps (∆951 [IQR -378-2323], p <0.001 and (∆1392 [IQR -609-4444], p = 0.02, respectively). Patients with classical LFLG-AS showed no statistically relevant improvement of daily steps (∆192 [IQR -687-770], p = 0.79). Patients with NFLG-AS showed a numerical decline in daily steps without statistical significance (∆-300 [IQR -1334-1406], p = 0.67). This first prospective study of this sample size shows significant improvement of physical activity after TAVR with an objective and reproducible method. This was mainly driven by an improvement in patients with HG-AS and paradoxical LFLG-AS. Highlights: Patients physical activity improves 6-months after TAVR. There are differences between different types of aortic stenosis. Patients with high-gradient aortic stenosis improved significantly after TAVR. Patients with classical low-flow-low-gradient aortic stenosis did not improve.